A market share model of the Malaysian sawntimber and plywood exports - Othman, Mohd Shahwahid; Abdullah, Maisom; Judi, Saroni (Penerbit Universiti Kebangsaan Malaysia, 1991)
The objective of this paper is to estimate market share functions for Malaysian exports of sawntimber and plywood and to obtain estimates of their relative price elasticity of market share. The empirical evidence indicates that the estimates of relative price elasticity of Malaysian market share exceeded zero and are statistically significant, implying that avenues exist for Malaysian producers to increase their shares of the world market through price competition.